STRATEGI HOLISTIK IMPLEMENTASI EKSTRAKURIKULER PENCAK SILAT : BEST PRAKTICE PEMBENTUKAN KARAKTER SISWA DI SMP YPS PRABUMULIH - Wiwik Anita; Dhiniaty Gularso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study presents a comprehensive analysis of the holistic strategy implementation of Pencak Silat extracurricular as a best practice model for character building at SMP YPS Prabumulih. Amidst the contemporary challenges of adolescent moral degradation, this research aims to evaluate the effectiveness of traditional martial arts in instilling integrity and discipline. Adopting a qualitative methodology with a descriptive case study design, the primary focus is to explore the deep internalization of self-control values that are systematically aligned with the dimensions of the Pancasila Student Profile. Primary data were collected through in-depth interviews involving source triangulation, including high-achieving students, professional certified coaches, and parents to ensure an objective perspective. Furthermore, participatory observation was conducted to validate the consistency of students' daily behavior within the school environment. The results indicate that the program functions as a highly effective pedagogical instrument through the exemplary conduct (modeling) of coaches and routine habituation, which successfully transfers the noble values and philosophy of Pencak Silat into students' daily conduct organically. The success indicators of this implementation strategy are confirmed by significant positive behavioral changes, enhanced mental resilience, and notable non-academic achievements at the regional level. This study concludes that integrating local wisdom into school activities can serve as a superior model for developing interest-based and character-focused curricula. These findings provide practical contributions for educational institutions in designing extracurricular programs that are oriented not only toward physical agility but also toward the sustainable development of students' personality and noble character.